Early hematopoiesis and macrophage development. Issue 6 (December 2015) - McGrath, Kathleen E.; Frame, Jenna M.; Palis, James
Graphical abstract: Highlights: Multiple sources of tissue-resident macrophage emerge during embryogenesis. Adult microglia originate from unipotential yolk sac primitive macrophage progenitors. Later yolk sac-derived EMP initiate definitive myelopoiesis in the fetal liver. Most fetal-derived adult tissue-resident macrophages originate from EMP. Abstract: The paradigm that all blood cells are derived from hematopoietic stem cells (HSCs) has been challenged by two findings. First, there are tissue-resident hematopoietic cells, including subsets of macrophages that are not replenished by adult HSCs, but instead are maintained by self-renewal of fetal-derived cells. Second, during embryogenesis, there is a conserved program of HSC-independent hematopoiesis that precedes HSC function and is required for embryonic survival. The presence of waves of HSC-independent hematopoiesis as well as fetal HSCs raises questions about the origin of fetal-derived adult tissue-resident macrophages. In the murine embryo, historical examination of embryonic macrophage and monocyte populations combined with recent reports utilizing genetic lineage-tracing approaches has led to a model of macrophage ontogeny that can be integrated with existing models of hematopoietic ontogeny. The first wave of hematopoiesis contains primitive erythroid, megakaryocyte and macrophage progenitors that arise in the yolk sac, and these macrophage progenitors are the source of early macrophages throughout the embryo, including the liver. A second wave of multipotential erythro-myeloid progenitors (EMPs) also arises in the yolk sac. EMPs colonize the fetal liver, initiating myelopoiesis and forming macrophages. Lineage tracing indicates that this second wave of macrophages are distributed in most fetal tissues, although not appreciably in the brain. Thus, fetal-derived adult tissue-resident macrophages, other than microglia, appear to predominately derive from EMPs. While HSCs emerge at midgestation and colonize the fetal liver, the relative contribution of fetal HSCs to tissue macrophages at later stages of development is unclear. The inclusion of macrophage potential in multiple waves of hematopoiesis is consistent with reports of their functional roles throughout development in innate immunity, phagocytosis, and tissue morphogenesis and remodeling. Understanding the influences of developmental origin, as well as local tissue-specific signals, will be necessary to fully decode the diverse functions and responses of tissue-resident macrophages.